Identificação de assimetrias bilaterais dos membros inferiores por meio de salto vertical em plataforma de força - Fabiola Bertu Medeiros (2013)
Bilateral asymmetry (BA) is defined as lateral differences of kinetic or kinematic variables between the upper or lower limbs. Recently the use of force platforms in order to determine the ground reaction force (GRF) during vertical jumps has been suggested for the identification of BA of the lower limb because of the higher similarity of vertical jumps with sports movements than isokinetic assessment. The determination of lateral differences can be achieved by simultaneous, separate measurement of the GRF of the two legs or by sequential measurement of each leg using only one force plate. Thefore, the main aim of the study was to compare simultaneous measurements and sequential measurement methods, and as a secondary aim, determine the reliability of bilateral symmetry index, in both methods, and the reliability of dynamic variables in two synchronized force plates. 31 athletes, volleyball and soccer players, (age: 19±0,6 years; body mass: 73,29±11,17 Kg; height: 176,08±0,06 cm) performed six maximal countermovement jumps on two force platforms. The maximal force, maximal power and impulse were the dynamic variables analyzed. To compare the different procedures in the diagnosis of BA the X2 of McNemar was used to identify the correspondence of the diagnostic information. The interclass correlation coefficient (ICC 3,1) was used to determine the reliability of the dynamics variables, maximal force, maximal power and impulse, and of the ISB, in both procedures. There were no significant differences between the diagnostic information in sequential and simultaneous analysis The ICC values for the variables were between 0,85 and 0,90, and the ICC values for the ISB were between 0,61 and 0,96. It is concluded that the use of two force plates are a reliable for the dynamic variables and for the ISB. And there are no sufficient evidences to reject the hypothesis that the different procedures produce distinct results.